(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a contrastive investigation of the semantic structure of maxims in English and Uzbek, pointing to investigate the likenesses and contrasts in how intelligence, social values, and social standards are encoded within the two dialects. Drawing on the hypothetical systems of semantics, pragmatics, and cognitive etymology, the think about analyzes how etymological, conceptual, and social components connected to create meaning in sayings. The inquire about highlights the ways in which English and Uzbek proverbs reflect their particular social worldviews, with consideration to allegorical expressions, metaphorical developments, and evaluative components. Through comparative examination, the consider illustrates that whereas numerous maxims in both dialects share all inclusive topics such as ethical quality, human behavior, and life encounters their semantic organization, symbolism, and social references frequently vary, uncovering one of a kind designs of conceptualization and etymological encoding. The discoveries contribute to a more profound understanding of cross-cultural semantics, intercultural communication, and the cognitive components basic world renowned expressions, emphasizing the significance of culture in forming dialect and meaning.